Information communication technologies and electoral violence in Africa: Kenya case study - Gwala, Noxolo (My University, 2019)
Existing frameworks that seek to respond to the challenge of preventing and managing electoral violence often omit technology as a relevant factor. Yet there is resounding proof that technology has wielded a sizeable amount of influence in shaping voter behaviour and perceptions, mobilising support, lobbying and ultimately influencing electoral outcomes. The utilisation of technology is evidenced by many examples; such as the use of biometrics to register and identify voters, the establishment of situation rooms and drones that collect data in real time, campaigns messages that are sent via text messages, video footage, radio, internet and bots that are used to collect and transmit information. The main problem that this study seeks to interrogate is the bi-directional outcomes generated by the use of ICTs in elections. There are cases where ICTs have been deployed to ferment violence, whilst ICTs have also proven to be useful in preventing electoral violence. Therefore, there is a need for research that assesses how ICTs can be better harnessed as a tool for the prevention and reduction of electoral violence in Africa. Notably, by exploring the use of ICTs by actors in Kenya’s 2007, 2013 and 2017 elections, the study posits that collaboration and responsible use are key in the prevention of electoral violence. Moreover, the study highlights that the use of new ICTs in elections is important in the growing discourse about defining the parameters of electoral integrity.
A Research Report submitted at the Faculty of Humanities, University of the Witwatersrand, Johannesburg, in partial fulfilment for the degree of Master Arts in International Relations Johannesburg, 2019
Keywords: Elections--Kenya; Information technology--Social aspects--Kenya; Voting--Kenya; Electronic voting--Kenya